THE EFFECT OF LIQUIDITY, LEVERAGE, PROFITABILITY ON THE VALUE OF MANUFACTURING COMPANIES IN INDONESIA THROUGH DIVIDEND POLICY - Siti Dini; Ester Stiovani Matius Liwa; Indah Yanti Rodearni; Alvira Azzahra; Ratna Sari Dewi (Jurnal Ipteks Terapan, 2023)
Objective study This To use For know influence liquidity , leverage , profitability to mark company manufacturing in Indonesia through policy dividends contained in the sector the Indonesian stock exchange (IDX) industry in 2019-2021. This research using 48 companies with 144 data during three year . Study This use purposive sampling method . Testing analysis used _with analysis multiple linear regression . Result of study This showing that liquidity , leverage , profitability influential positive to variable mark company through policy dividend.Accordingly Partial liquidity influential positive to mark company whereas leverage , profitability , policy dividend No effect and not significant to mark company